1997
DOI: 10.1126/science.277.5327.815
|View full text |Cite
|
Sign up to set email alerts
|

An Antagonist Decoy Receptor and a Death Domain-Containing Receptor for TRAIL

Abstract: TRAIL, also called Apo2L, is a cytotoxic protein that induces apoptosis of many transformed cell lines but not of normal tissues, even though its death domain-containing receptor, DR4, is expressed on both cell types. An antagonist decoy receptor (designated as TRID for TRAIL receptor without an intracellular domain) that may explain the resistant phenotype of normal tissues was identified. TRID is a distinct gene product with an extracellular TRAIL-binding domain and a transmembrane domain but no intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
1,135
4
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,398 publications
(1,156 citation statements)
references
References 22 publications
11
1,135
4
6
Order By: Relevance
“…Both recombinant, soluble TRAIL and wild-type, membrane-bound TRAIL induce apoptosis in a wide variety of transformed cell lines via interaction with one or both of the death receptors DR4/TRAIL-R1 and DR5/TRAIL-R2, 12,13 which in turn initiates activation of caspase-8 through FADD, leading to apoptosis. [14][15][16] However, the antagonistic decoy receptors DcR1, 17,18 DcR2, 19 and osteoprotegerin 20 are believed to protect normal cells from the cytotoxic effects of TRAIL by competing with DR4/TRAIL-R1 and DR5/TRAIL-R2 for TRAIL binding.…”
Section: In Either Dld1/bax-r or Dld1/trail-r Cells Bcl-xl Expressiomentioning
confidence: 99%
“…Both recombinant, soluble TRAIL and wild-type, membrane-bound TRAIL induce apoptosis in a wide variety of transformed cell lines via interaction with one or both of the death receptors DR4/TRAIL-R1 and DR5/TRAIL-R2, 12,13 which in turn initiates activation of caspase-8 through FADD, leading to apoptosis. [14][15][16] However, the antagonistic decoy receptors DcR1, 17,18 DcR2, 19 and osteoprotegerin 20 are believed to protect normal cells from the cytotoxic effects of TRAIL by competing with DR4/TRAIL-R1 and DR5/TRAIL-R2 for TRAIL binding.…”
Section: In Either Dld1/bax-r or Dld1/trail-r Cells Bcl-xl Expressiomentioning
confidence: 99%
“…This is a homolog to Fas and tumor necrosis factor-R1, and is required for TRAIL-induced apoptosis. [6][7][8] On the other hand, TRAIL also binds to DcR1 and DcR2 that sequester the ligand, but are unable to initiate an apoptosis signal. Thus, DcR1 and DcR2 are considered to be the decoy receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Decoy receptors lack the death domain portion of the molecule, and therefore act as an antagonist to the DR4 and DR5 receptors. 4,[34][35][36][37] In a previous publication we demonstrated that Fas-induced apoptosis is not blocked by overexpression of bcl-2. 30 More recently, we demonstrated that TNF␣-induced apoptosis in myeloma cells is also resistant to bcl-2.…”
Section: Trail Is Not Cytotoxic To Freshly Isolated Cd34 + /Cd45 Dim mentioning
confidence: 89%